Recent management of endometrial cancer: a narrative review of the literature - Pados, George; Zouzoulas, Dimitrios; Tsolakidis, Dimitrios (Frontiers in Medicine, 2024)
Endometrial cancer is a common female gynecological neoplasia and its incidence rate has increased in the past years. Due to its predominant symptoms, most women will present uterine bleeding. It is usually diagnosed at an early stage and surgery has an important role in the treatment plan. The prognosis and quality of life of these patients can be quite favorable, if proper treatment is offered by surgeons. Traditionally, more invasive approaches and procedures were offered to these patients, but recent data suggest that more conservative and minimal invasive choices can be adopted in the treatment algorithm. Minimal invasive surgery, such as laparoscopy and robotic surgery, should be considered as an acceptable alternative, compared to laparotomy with less comorbidities and similar oncological and survival outcomes. Furthermore, sentinel lymph node biopsy has emerged in the surgical staging of endometrial cancer, in order to replace comprehensive lymphadenectomy. It is associated with less intra- and postoperative complications, while preliminary data show no difference in survival rates. However, sentinel lymph node biopsy should be offered within a strict algorithm, to avoid residual metastatic disease. The aim of this review is to analyze all the available data for the application of minimal invasive surgery in early endometrial cancer and especially the role of sentinel lymph node biopsy.